Answer:
[tex]\tan \theta[/tex]
Step-by-step explanation:
We have to simplify the following expression as given by
[tex]\sin \theta \times \sec \theta[/tex]
= [tex]\frac{\sin \theta}{\cos \theta}[/tex]
= [tex] \tan \theta [/tex] ( Answer )
Because, we know that [tex] \sec \theta =\frac{1}{\cos \theta}[/tex] and [tex] \tan \theta = \frac{\sin \theta}{\cos \theta}[/tex]
If we consider [tex]\sin \theta = \frac{Perpendicular}{Hypotenuse}[/tex] and [tex]\sec \theta = \frac{Hypotenuse}{Base}[/tex],
then [tex]\sin \theta \times \sec \theta = \frac{Perpendicular}{Hypotenuse}\times \frac{Hypotenuse}{Base} = \frac{Perpendicular}{Base}= \tan \theta [/tex]